Nicht-phonologisch konditionierter Wandel in der Kasusmorphologie isolierter germanischer Varietäten.: Höchstalemannisch (Visperterminen) und Älvdalisch - Baechler, Raffaela; Pröll, Simon (Linguistik Online, 2019)
This article deals with structure and change of the nominal case systems of two isolated Germanic varieties, Visperterminen Alemannic (Valais, Switzerland) and Övdalian (Älvdal, Sweden). As both varieties inherited and retained the full vocalism in unstressed syllables of their predecessors (Old High German and Old Swedish, respectively), they provide a suitable testing ground for the examination of processes of morphological change independently of phonological processes. By comparing the particular changes in nominal inflection we analyse syncretisms, inflectional reductions and (purely morphological) strategies for compensating syncretisms in both varieties.Despite different trajectories of case loss, both varieties yield strikingly parallel results in terms of compensation at the level of the noun phrase. The modern noun system displays nominative-accusative syncretism in the singular (minor exceptions in Övdalian) and plural, as well as nominative/accusative-dative syncretism in the singular (minor exceptions in both varieties), caused by one of two factors: We can observe that a new, non-phonologically conditioned collapse and reorganisation of inflection developed, but there is also inherited syncretism, dating back to the Middle Ages. Meanwhile, at the level of the full noun phrase (i. e. including the article and the adjective), the dative is still clearly marked as an oblique case, whereas nominative and accusative syncretise.The diachronic comparison of these two isolated varieties with their historical precursors shows that these changes in the respective case systems – towards a ± dative system – are to be regarded as a process that is largely internal to morphology, as it is neither a side effect of phonological change nor the result of contact.